Research on the generation mechanism and characteristics of an Energy Internet backbone network - Li, Xiaopeng; Zhang, Zheng; Zhou, Yucheng; Li, Peng; Ji, Liyan (Frontiers in Physics, 2023)
-This reviewer feels that the actual contribution and results in this paper are poor. What is the challenge of designing such a topology generation and evolution mechanism?After discussion, the project team believes that the lack of description of the research problem context in the paper can easily cause inconvenience to readers. Therefore, the project team greatly appreciates your direct indication of this issue, and at the same time, we would also like to request your permission to provide a clearer explanation of our research contribution to the paper:The project team conducted in-depth research based on the existing macro topology of the energy Internet, and referred to HUHM and Complex Hybrid networks as the evolution mechanism. We extracted the dumbbell like commonness of the real power grid as the structural basis, and proposed the HRNA evolution mechanism according to the characteristics of hierarchical regional autonomy of the Energy Internet. The structure of the paper is shown in the figure below.